Faire connaissance avec une mulier religiosa dans les Pays-Bas méridionaux du xiiie siècle - Anne-Laure Méril-Bellini delle Stelle (Bulletin du Centre d’Études Médiévales d’Auxerre)
In the thirteenth-century Southern Low Countries, the mulieres religiosae played an important part in religious life and were fervently wanted to be met, since they were well known for being great thaumaturgists or intercessors “sending God” to anybody. Their hagiographer provide evidence of this, by through scenes of first meeting which illuminate in a new light the principles of sociability of these devout women. Identifying the canvas allows indeed to better understand their place and role among their contemporaries, or at least those that the ecclesiastical reformers would see them assume. Thus, behind the topoi of the reputation of holiness and the divine intercession exerted through them, a range of social practices and of specific relationship emerge as a watermark of these scenes.